MENGELOLA KEBERAGAMAN PEGAWAI DALAM KONFLIK INTERPERSONAL GUNA MENINGKATKAN PRODUKTIVITAS KARYAWAN: STUDI KOMPARASI - Syamsuar, Candra Aldilla; Ginting, Henndy (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2020)
Employee diversity when managed appropriately may contribute to organization to create more effective and productive organization. Thus the organization can compete and dealt with the change and face the dynamic environment. The importance of managing diversity is needed for organization to adapt and compete with the competitor in any circumstances. This research using qualitative study to as methodology, the data collection were gathered using open-ended interview and analysis tool using coding technique. Findings shows that by managing conflict especially conflict that caused by the diversity could emphasize the productivity and the achievement of the organization. Despite the inter-personal relation and inter-personal conflict, the achievement of the employee may be higher than usual.Â